Research on the Effect of Revitalizing Homestead for Realizing Long-term Poverty Alleviation under the Background of Rural Revitalization - Wu, Hailing; Lin, Zesen; Wu, Ruiyao; Zhang, Xuelin; Weng, Yulin; Lu, Yongshan; Zhou, Nanchang; Huang, Xiying; Cheng, Yiyuan; Zhang, Xiao; et al. (Advances in Social Sciences Research Journal, 2022)
With the progress of industrialization and urbanization and the successful completion of the battle against poverty in 2020, China has achieved a feat in the history of poverty alleviation, and this is followed by a critical period for winning the battle against poverty and realizing the goal of rural revitalization. The first thing to solve is the problem of "agriculture, rural areas and farmers". In the problem of "agriculture, rural areas and farmers", what is more difficult is how to effectively use the idle homestead land and how to better solve the phenomenon of wasted land resources. In view of this, this paper tries to explore the feasible method suitable for revitalizing idle rural homestead in Guangdong Province from the successful cases of local trial sites as the basic data, starting from the idle homestead. It provides a feasible way to revitalize the idle rural homestead in most areas of our province to achieve long-term poverty alleviation. This article is arranged as follows: The first part mainly explains the economic development analysis under the background of rural revitalization, the second part mainly analyzes the utility of the homestead for rural revitalization, the third part analyzes the current situation of poverty-stricken villages in the province, the fourth part introduces our path analysis of revitalizing homestead under rural revitalization, the fifth part is to provide the conclusion of revitalizing the homestead for reference.